Simulator Modules for Learning Maintenance of Avionics Components in Solid State Cockpit Voice Recorder (SSCVR) PN. 980-6022-001 and Aircraft Battery PN. 405CH - Dwinny Puspa Dinar Saputri; Dwi Nugraheny (Institut Teknologi Dirgantara Adisutjipto, 2019)
PT GMF AeroAsia Tbk is an international company that provides the largest maintenance facilities and services in Asia. The divisions in PT GMF AeroAsia Tbk one of which is the Avionics Shop division, where the division is a part that performs maintenance of avionics components such as Solid State Cockpit Voice Recorder (SSCVR), Flight Data Recorder (FDR), Aircraft Battery and all other electronic components that is in the plane. At the Avionics Shop at PT GMF AeroAsia Tbk for the maintenance training needs of the avionics component, a simulator is needed as a learning media about the process of introducing, assembling and dismantling a PN Solid State Cockpit Voice Recorder (SSCVR) component. 980-6022-001 and Aircraft Battery PN. 405CH. The simulator is built using Unity 3D and asset modeling using Blender. The results of the functionality test state that the simulator can run well according to its function. The results of the due diligence obtained an average value of 90.4 which is included in the category of